2015
DOI: 10.4236/wjns.2015.54025
|View full text |Cite
|
Sign up to set email alerts
|

Examine the Relationship of Emotional Intelligence and Creativity with Academic Achievement of Second Period High School Students

Abstract: The present study aimed to examine the relationship of emotional intelligence and creativity with academic achievement of second period high school students in Nikshahr. This was a descriptive-correlational study. The population of the current study included all second period high school students in the academic year of 2013-2014. The statistical sample was selected using simple random sampling method. To collect data, Mayer Salovey Caruso Emotional Intelligence Test (1995) as well as Creativity Questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Research shows that low level relationship between achievement and creativity (Erdoğdu, 2006;Kara, 2011), positive and meaningful relationship (Anwar, Aness, Khizar, Naseer, & Muhammad, 2012;Ayverdi, Asker, Öz Aydın, & Sarıtaş, 2012;Florence, Mark, & Samuel, 2015;Gautam, 2017;Jenaabadi, Shahidi, Elhamifar, & Khademi, 2014;Naderi, Abdullah, Aizan, Sharir, & Kumar, 2010;Nami, Marsooli, & Ashouri, 2014;Niaz, Núñez, & Pineda, 2000), that there is a strong relation (Yeh, 2004), that there is no relation (Balgiu & Adîr, 2013;Olatoye, Akintunde, & Yakasai, 2010;Tatlah, Aslam, Ali, & Iqbal, 2012) and negative and meaningful relationship (Olatoye, Akintunde, & Ogunsanya, 2010). According to Gautam (2017), academic success is positively and significantly related to the different dimensions of creative thinking (flexibility, fluency, originality and total creativity).…”
Section: Discussionmentioning
confidence: 99%
“…Research shows that low level relationship between achievement and creativity (Erdoğdu, 2006;Kara, 2011), positive and meaningful relationship (Anwar, Aness, Khizar, Naseer, & Muhammad, 2012;Ayverdi, Asker, Öz Aydın, & Sarıtaş, 2012;Florence, Mark, & Samuel, 2015;Gautam, 2017;Jenaabadi, Shahidi, Elhamifar, & Khademi, 2014;Naderi, Abdullah, Aizan, Sharir, & Kumar, 2010;Nami, Marsooli, & Ashouri, 2014;Niaz, Núñez, & Pineda, 2000), that there is a strong relation (Yeh, 2004), that there is no relation (Balgiu & Adîr, 2013;Olatoye, Akintunde, & Yakasai, 2010;Tatlah, Aslam, Ali, & Iqbal, 2012) and negative and meaningful relationship (Olatoye, Akintunde, & Ogunsanya, 2010). According to Gautam (2017), academic success is positively and significantly related to the different dimensions of creative thinking (flexibility, fluency, originality and total creativity).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a meta‐analysis with a total sample size of 18,130 conducted by Xu et al (2019) revealed that the relationship between emotional intelligence and creativity is moderately significant. (Alfonso‐Benlliure et al, 2021; Bartlett, 2015; Chan, 2005; Darvishmotevali et al, 2018; Geher et al, 2017; Guastello et al, 2004; Jenaabadi et al, 2015; Khalid & Zubair, 2014; Sánchez‐Ruiz et al, 2011; Silva & Coelho, 2019; Tsai & Lee, 2014). On the other hand, there are also others who found either no or weak significant relationships between the two (Ivcevic et al, 2007; Lee et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Furnham (2016) studied the relationship between IQ, EQ and creativity and concluding Cognitive ability or IQ correlated positively but not significantly with creativity but significantly negatively with emotional intelligence. Jenaabadi (2015) aimed to examine the relationship of emotional intelligence and creativity with academic achievement indicating a high correlation between emotional intelligence and academic achievement and between creativity and academic achievement, but showing no significant difference was found between males and females considering their academic achievement. Ivcevic (2007) examined the relationship between emotional intelligence (EI) and emotional creativity (EC) and their effect on creative behavior.…”
Section: Literature Reviewmentioning
confidence: 99%